A Few Notes on C.S. Lewis’s Understanding of the Tao - Mihaela Cernăuți-Gorodețchi (Linguaculture, 2019)
In his series of three lectures delivered at King’s College, Newcastle, part of the University of Durham, in February 1943 and published the following year under the title The Abolition of Man; or, Reflections on Education with Special Reference to the Teaching of English in the Upper Forms of Schools, C.S. Lewis passionately argues for the preservation or reinstatement of “the sole source of all value judgements”, represented, in his opinion, by “traditional values”, that he calls “for convenience the Tao, and which others may call Natural Law or Traditional Morality or the First Principles of Practical Reason or the First Platitudes.” This article looks a little closer at the specific meaning of the Tao selected (and then adapted) by C.S. Lewis from a rather complex and fluid philosophical paradigm informed by two contrasting (Taoist and Confucian, respectively) schools of thought.